The Effectiveness of Flipped Learning During the Pandemic to Improve the Writing Competence of STMIK STIKOM Indonesia Students - Kadek Yogi Susana; A A Gede Raka Wahyu Brahma (RETORIKA: Jurnal Ilmu Bahasa, 2021)
Characteristically flipped learning enables students to utilize their time in class schedule to have discussion and elaborate their analysis especially in writing. The students can obtain learning experience which will shape their English. The research was aimed to determine the effectiveness and impact of flipped learning on developing writing competence of students during the COVID-19 pandemic. There are 32 fourth semester students majoring in Informatics Engineering STMIK STIKOM Indonesia who are the objects of this research. This research was conducted in the form of CAR (Class Action Research) which included the stages of planning, implementing action, observation and reflection which were carried out in two cycles. This study adopts the three-stage model proposed by Estes et al. (2015) for flipped learning: pre-class, in-class and post-class stages. Quantitative data were acquired from the eventual outcomes of convincing articles arranged by the students when the usage of flipped learning. Quantitative data, especially three kinds of data; (pre-test and post-test 1), (pre-test and post-test 2) and (post-test1 and post-test2) were examined utilizing SPSS 21 statistics. The correlation coefficient (r) for the principal informational index was 0.769 and the subsequent informational index was 0.907. The scope of all the correlation coefficients infers that there is an intensive connection among when the use of flipped learning. In view of the aftereffects of the examination utilizing SPSS statistics 21 with a certainty level of 95%, it is realized that H1 is acknowledged and H0 is dismissed, implying that there is a huge impact on the use of flipped learning in improving students’ writing ability.